2015
DOI: 10.1002/jbm.a.35561
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic potential of physically treated bovine cartilage matrix derived porous scaffolds on human dermal fibroblast cells

Abstract: Extracellular matrices have drawn attention in tissue engineering as potential biomaterials for scaffold fabrication because of their bioactive components. Noninvasive techniques of scaffold fabrication and cross-linking treatments are believed to maintain the integrity of bioactive molecules while providing proper architectural and mechanical properties. Cartilage matrix derived scaffolds are designed to support the maintenance of chondrocytes and provide proper signals for differentiation of chondroinducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The behavior of cells and physical properties of the scaffolds can be affected by different crosslinking schemes . Rowland et al reported that physical crosslinking, specifically DHT crosslinking, resulted in better chondrogenic response from encapsulated MSCs than did chemical crosslinking .…”
Section: Postdecellularization Processing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior of cells and physical properties of the scaffolds can be affected by different crosslinking schemes . Rowland et al reported that physical crosslinking, specifically DHT crosslinking, resulted in better chondrogenic response from encapsulated MSCs than did chemical crosslinking .…”
Section: Postdecellularization Processing Methodsmentioning
confidence: 99%
“…63 The behavior of cells and physical properties of the scaffolds can be affected by different crosslinking schemes. 62,67 Rowland et al reported that physical crosslinking, specifically DHT crosslinking, resulted in better chondrogenic response from encapsulated MSCs than did chemical crosslinking. 62 However, a study conducted by Almeida et al showed chemical crosslinking did not limit the chondroinductive capacity when compared to a scaffold crosslinked via DHT.…”
Section: Cartilagementioning
confidence: 99%
“…Even though endochondral bone formation was observed after scaffolds were subcutaneously implanted in rats for 11 weeks, BM‐MSCs had started forming cartilage‐like matrix that was rich in GAGs only after the in vitro culture. Moradi et al . likewise used UV irradiation but combined the irradiation with DHT treatment to crosslink scaffolds from shattered, homogenized, and decellularized bovine articular cartilage that had been freeze dried in cylindrical molds.…”
Section: Decellularized Cartilage Matrixmentioning
confidence: 99%
“…Physical crosslinking techniques such as dehydrothermal treatment [18, 35, 36] or ultraviolet irradiation [18, 19, 21, 35, 36] have also been applied to prevent cell-mediated contraction of CDM scaffolds. Furthermore, these physical crosslinking treatments have been shown to preserve epitopes that participate in cell-matrix interactions, and supported greater chondrogenic differentiation than chemically crosslinked scaffolds [18].…”
Section: Introductionmentioning
confidence: 99%